Hemp From Disordered Lines for New Staple Fibre Yarns and High-Performance Composite Applications - Graupner, Nina; Weber, David E.; Bell, Erik G.; Lehmann, Karl-Heinz; Hilgers, Hans-Willi; Randerath, Herbert; Gries, Thomas; Walenta, Isabel; Joulian, Marc; Müssig, Jörg (Frontiers in Materials, 2022)
The present study deals with developing yarns from cost-effective hemp from a disordered separation process (total fibre line) for composite materials. Yarns from the rotor spinning process and yarns with almost unidirectional fibre orientation in the core were produced from the staple fibres to achieve a good reinforcement effect. Composites were produced from the yarns using a miniature pultrusion process. The best reinforcement effect was achieved with the staple fibre yarns. The results show that around 90% of the flexural strength and flexural modulus of identically produced flax composites could be achieved with maximum values of 282 MPa for the flexural strength and 23.4 GPa for the flexural modulus. But the impact strength is a deficit; only slightly more than 55% of the flax fibre-reinforced composite could be achieved. The yarns were used to produce quasi-unidirectional fabrics for the production of composite laminates using industrial manufacturing processes. In addition, hybrid materials were produced from glass and hemp fabrics. With the hemp composites, good results were also achieved in terms of tensile and bending properties. However, the impact strength still needs to be improved. By producing hybrid materials from hemp and glass, the characteristic values and especially the impact strength could be significantly improved. Overall, it has been shown that good characteristic values can be achieved with low-cost hemp when an appropriate preparation is done. The characteristic values are sufficient to use the materials in applications with higher mechanical requirements.